UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI GROUP INVESTIGATION (GI) - Supriyadi, Teguh; Muhfahroyin, Muhfahroyin (Bioedukasi Jurnal Pendidikan Biologi, 2014)
Learning achievement is a students capability while and after accept learning experience learning. Learning process involved students activity is needed, so that to give the meaning and the real learning of students. GI cooperative learning model is a learning model involved whice all of students activity in learning process. In learning process the students find knowledge independenly because they are active and teacher just only as a facilitator. The conclusion of this research is the GI cooperative learning model can improve the result of study students XI IPA SMA Kosgoro Sekampung school year 2011/2012 from pre-classroom action research to the second cycle for 47,37% and researcher suggests that the GI cooperative learning model can be used to increase learning achievement of biology learning. Kata Kunci: Group Investigation, Aktivitas Belajar, Hasil Belajar